Desidratação de suco de abacaxi probiótico por spray dryer - Almeida, Francisca Diva Lima (2012)
Recent researches show the potential use of fruit juices as an excellent way to carry probiotic microorganisms. Thus, the aim of the following study was to develop a new non-dairy probiotic food from of pineapple juice containing Lactobacillus casei NRRL B-442 dehydrated by spray-drying process. Firstly, the pineapple juice underwent a heat treatment (90 ° C / 1 minute) in order to inactivate the proteases present in the juice and evaluate the influence of enzyme inactivation on the microorganism survival. Subsequently, the employment of three temperatures (150, 120 and 100 ° C) on the juice dehydration was appraised, with the purpose of defining an appropriate temperature based on the microorganism survival, after the dehydration process. Other parameters were also studied, such as: the effect of addition of different materials (gelatin, gum arabic, maltodextrin), which were used as protective agents for the microorganism, as well as the concentration of each tested adjuvant. Viability of L. casei (before and after the drying process), powder yield and rehydration levels and the color of the reconstituted juice were also assessed. Based on the attained results, it can be concluded that the utilization of lower temperatures (100 ° C) and the appliance of heat treatment in the juice favored the survival of L. casei after dehydration. Excellent levels of microorganism survival after the drying process were achieved by using 10% gelatin and 5% gum arabic as protective agents, thus showing a promising possibility of formulating a new powder probiotic food without the restrictions inherent in dairy products.